THE SCIENCE OF PRINCIPLES AND PRACTICES LEADING TO THE LAW OF TRUTH - PhramahaWeerapat Theingthea; Phrakruworakanchanachoti (Chalong Jotivaro) (Journal of Contemporary Buddhist Society = JCBS, 2024)
This academic article is addressing the issue Buddhism is the world's dominant religion teachings that are like the great river of all sciences So it's not just a philosophy or a theory. but still has content covering the way of life The existence of thoughts in almost every aspect Not a religion of prayer or religion of worry The Buddha's teaching of the Dhamma is practically aimed at everyone dealing with the real life in the world. In today's Thai society in the era of Thailand ๔.๐, this is a trend that has been addressed. and analyzed in many aspects, probably due to the policy vision of the government that will drive Thailand towards the goal of "Stable, Prosperous, Sustainable", especially Policies to transform the traditional economy into a technology and innovation.